2017
DOI: 10.1136/bmjinnov-2016-000140
|View full text |Cite
|
Sign up to set email alerts
|

Engaging patients through an iBooks-based patient portal tutorial

Abstract: IntroductionPatient portals or personal health records allow patients to access their health information and communicate with their physician’s office outside of their clinic visit. As such, their use has been observed to increase patient engagement and decrease administrative costs. Despite these advantages, patient adoption and successful use of patient portals remains low. Here we assess the feasibility and efficacy of an iBooks-based tutorial in increasing comfort and compliance with personal health record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Additionally, Arcury et al (2017) found that interventions providing education, social support, and allow for frequent internet utilization improved the use of patient portals; Casey. (2016) found that adult patients with chronic disease were more likely to use a portal personal health record following an educational intervention than patients who had not received the intervention; and Leisy et al (2017) determined that a 5-minute iBook-based tutorial describing the institution's patient portal increased comfort levels in knowledge on using the portal, knowledge about the portal's existence, and intent to use the patient portal among ophthalmology clinic patients. These are perfect examples of where this work can begin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Arcury et al (2017) found that interventions providing education, social support, and allow for frequent internet utilization improved the use of patient portals; Casey. (2016) found that adult patients with chronic disease were more likely to use a portal personal health record following an educational intervention than patients who had not received the intervention; and Leisy et al (2017) determined that a 5-minute iBook-based tutorial describing the institution's patient portal increased comfort levels in knowledge on using the portal, knowledge about the portal's existence, and intent to use the patient portal among ophthalmology clinic patients. These are perfect examples of where this work can begin.…”
Section: Discussionmentioning
confidence: 99%